The role of Tenascin-X, Paraoxonase 1 and some other biochemical parameters in infertility women - Yasameen Abdulhuussien Salman; Saif. M. Hasan; Nagham Qasim Kadhim (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
The thyroid interact with the hypothalamic-pituitary reproductive axis. Tenascins (TN) are a group of versatile glycoproteins found in the extracellular matrix (ECM) that have distinct expression patterns in different tissues and stages of development, as well as in homeostasis tissue balance and during infections and diseases. Furthermore there  are   four types of  family members that are referred as  tenascin (-C,-R,-X, -W).Tenascin-X and tenascin-C have significant involvement in human diseases. The paraoxonase family consists of three genes: paraoxonase 1, paraoxonase 2, and paraoxonase 3. These genes have around 70% genetic sequence similarity and 60% same sequence of amino acid. Materials and Methods: 120  Sample of the current study were collected from married women aged 20 and 45 years after taking their information (age, height, weight, and health status in detail) to obtain suitable samples.  Results : The anti-mullerian hormone showed significant decrease at (P<0.01) in hypothyroidism and increase significant in infertility at (P<0.01). Prolactin showed highly increase significant in hypothyroidism at (P<0.01) and in infertility women patients compared with women control . Luteinizing hormone level showed increase significant in hypothyroidism and infertility at (P<0.01)  and follicle-Stimulating hormone level showed decrease significantly .The tenascin-X showed a high significant increase at (P<0.01) in  hypothyroidism patient compared with control group. The optimal cut-off value tenascin-X was (10.382 pg/ml as cut-off value). The tenascin-X showed a high significant increase at in infertility with hypothyroidism women patient compared with control group. The optimal cut-off value for tenascin-X was (8.904 pg/ml) . Albumin level showed decrease significant in hypothyroidism at (P<0.01) and increase significant in hypothyroidism and infertility patients at (P<0.01) with control group. Conclusions: Hypothyroidism is associated with changes in the level of sex hormones, which is one of the main causes of infertility . tenascin-X were related with hypothyroidism. Hypothyroidism is associated with oxidative stress, PON-1conseder anti-oxidant and activity is changes in oxidative stress of different etiology.